Fikih Gaming: Studi Fatwa MPU (Majelis Permusyawaratan Ulama) Aceh Nomor 3 Tahun 2019 Tentang Hukum Game PUBG (Player Unknown’s Battle Grounds) Perspektif Sadd al-Z|ari>’ah - Rofi Ulwan S.; Abdullah Faqih (Wasathiyyah, 2023)
Fatwas have an important role for the lives of Indonesian Muslim communities. Fatwa is a guideline in dealing with or answering problems that have not happened before. In addition to the MUI, there is also the Aceh Ulema Consultative Assembly (MPU) which is quite responsive in providing religious views on contemporary issues. One of them is the Aceh MPU fatwa regarding the PUBG (Player Unknown's Battle Grounds) Game Law number 03 of 2019. The fatwa was motivated by the high level of addiction of some people to the online game. This review will review the verdict of the Aceh MPU fatwa with the review of Sadd al-z|ari>’ah. This research, including library research by adapting descriptive-qualitative studies. This study concluded that MPU Aceh based its fatwa on the impact and consequences that will occur for its players. MPU Aceh views that PUBG game has a bad impact on its players. In addition, it can lead to changes in behavior to negative, aggressive and addictive at a dangerous level. In order to avoid these adverse effects, MPU Aceh decided that the law of playing PUBG Mobile Game is haram. Thus, the decision of the MPU fatwa on the law of playing online games (PUBG) is in line with the rules of Sadd al-z|ari>’ah.